The secret life of hidden places : concealed rooms, clandestine passageways, and the curious minds that made them - Bachmann, Stefan, 1993-; Tucholke, April Genevieve (Workman Publishing, 2023)
"A spellbinding tour, filled with stories and photographs, of some of the world's most fascinating architectural mysteries. This wondrous guide for the curious and the intrepid takes readers on a lushly photographed and lyrically written tour of eighteen of the world's most captivating architectural mysteries. Delve into both the secretive places themselves and the eccentric and obsessive minds that created them. Visit a chamber of skulls high in the Swiss Alps, a Japanese temple full of traps, a Parisian apartment locked and untouched since World War II, a Prohibition-era speakeasy in Washington, DC, and a spooky "initiation" well in Portugal built by a secret society. How far down can you climb before losing your nerve?